THE RESULTS OF THE PROGRAM OPTIMIZATION OF THE MOTIVATIONAL-SEMANTIC SPHERE FOR PATIENTS WITH DIABETES - Krupelnytska Liudmyla Frantsivna; Burovska Iryna Oleksandrivna (International Journal of Innovative Technologies in Social Science, 2021)
The article shows the approbation results of the program optimization of the motivational-semantic sphere for patients with diabetes mellitus. The main content of the program and the results of the research are presented using the test "Meaning and life orientations" by D. Leontiev, the method "Diagnosis of the motivational structure of personality" by V. Milman and "The color test of attitudes" by A. Etkind. The study involved 79 people, mean age - 55.86, σ - 16.72. There is an increase in indicators of motives for communication and community usefulness that provide compensation for socio-psychological problems caused by the disease; goals in life, process and locus of control-I. These changes can be considered as markers of optimization of the motivational and semantic sphere of these persons. In the comparison group, the changes differ significantly from the changes in the main group: the indicators of the motive for communication, goals in life and the locus of control-I have increased. But there is a paradoxical combination of the locus of control-I growth with a simultaneous significant decrease in the locus of control-life. It can be explained, on the one hand, by improving physical condition and, accordingly, expanding the perspective of Future of these people, on the other hand, strengthening the belief that their somatic well-being depends on other people and circumstances, not on themselves. Disease’s emotional assessment intensity, under the psychocorrection program influence, decreased in the main group, while, on the contrary, there was simultaneous increasement in the comparison group. Emotional evaluation of the Present for respondents from the main group increased after the program; on the contrary, for those in the comparison group, this indicator decreased. The value of the Future in both groups increased for the first week of stay in the treatment center, but growth was more intense for the main group.